2008
DOI: 10.1109/tit.2008.920190
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Sensing and Redundant Dictionaries

Abstract: Abstract-This article extends the concept of compressed sensing to signals that are not sparse in an orthonormal basis but rather in a redundant dictionary. It is shown that a matrix, which is a composition of a random matrix of certain type and a deterministic dictionary, has small restricted isometry constants. Thus, signals that are sparse with respect to the dictionary can be recovered via Basis Pursuit from a small number of random measurements. Further, thresholding is investigated as recovery algorithm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
354
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 480 publications
(364 citation statements)
references
References 23 publications
9
354
0
1
Order By: Relevance
“…where C is a given constant, then δ k ≤ ǫ k with high probability [7,9,18]. A similar result for the same family of random matrices holds for the D-RIP [14].…”
Section: Algorithm Guaranteessupporting
confidence: 54%
See 1 more Smart Citation
“…where C is a given constant, then δ k ≤ ǫ k with high probability [7,9,18]. A similar result for the same family of random matrices holds for the D-RIP [14].…”
Section: Algorithm Guaranteessupporting
confidence: 54%
“…This result also implies perfect recovery in the absence of noise. It was extended also for incoherent redundant dictionaries [9]. An alternative aproach to approximating (2) is to use a greedy strategy.…”
Section: Algorithm 1 Signal Space Cosamp (Sscosamp)mentioning
confidence: 99%
“…Compressed sensing (CS) aims to find a sparse solution to the problem in (1), where most of the elements of the solution vector x are zero [3,4]. Compressed sensing algorithms can be divided into two broad categories: (i) Single Measurement Vector (SMV) [5], [11] where the solution is a vector; and (ii) Multiple Measurement Vectors (MMV) [9], [10] where the solution is a two-dimensional array, or matrix.…”
Section: Compressed Sensingmentioning
confidence: 99%
“…This problem can be described mathematically as follows: given an original signal y in an n-dimensional space and a set of basis vectors, find, within a preset tolerance, a compact representation of y using the subspace spanned by the basis vectors. The development of pursuit algorithms such as orthogonal matching pursuit [5] from compressed sensing [3,4], with the capability to find a sparse representation, has offered new approaches for tackling the aforementioned problem. Using an over-complete dictionary D consisting of k basis vectors or atoms, the original signal can be decomposed by solving the following system of linear equations:…”
Section: Introductionmentioning
confidence: 99%
“…For the incomplete data situation, the mathematical technology called compressive sensing, which turned out to be quite successful in sparse signal recovery, was established several years ago by D. Donoho, see [18]. A major breakthrough was achieved when it was proven that it is possible to reconstruct a signal from very few measurements under certain conditions on the signal and the measurement model, see [8,9,10,19,20,18,24,42]. In [12] it was shown that if the sensing operator satisfies the restricted isometry property the solution can be reconstructed exactly by minimization of an 1 constrained problem, provided that the solution is sparse enough.…”
Section: Introductionmentioning
confidence: 99%